Análise contrastiva dos verbos locativos do português do Brasil e do português europeu - Rodrigues, Roana (2016)
Locative verbs establish a locative relation between an object and a location and are very frequent in different types of texts. This thesis aims at describing the phenomenon of locative verb constructions in Portuguese and contrasting two recent studies on the syntactic-semantic classification of these constructions carried out for Brazilian and European Portuguese. This contrastive analysis presents not only the classes of locative constructions already determined, but also the intersection and divergence points between the two variants of the Portuguese language. The data here described is expected to contribute in the construction of language resources, which could be used in several didactic applications and in natural language processing.